2022
DOI: 10.3390/vetsci9110617
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition, Fermentation End-Product of Silage, and Aerobic Stability of Cassava Pulp Fermented with Lactobacillus casei TH14 and Additives

Abstract: This study evaluated the effects of cassava pulp fermented with Lactobacillus casei TH14, urea, and molasses on its chemical composition, the fermentation end-product of silage, and aerobic stability. A 2 × 2 × 2 factorial arrangement with a randomized complete block design was employed. The first factor: level of L. casei TH14 [L; 0 and 105 cfu/kg fresh matter (FM)], the second factor: level of molasses (M; 0 and 4% DM), the third factor: level of urea (U; 0 and 4% DM), and the number of days of fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Cassava pulp (CSVP) is a residue of the starch manufacturing process, which could produce up to 500 tons of CSVP per day and might be a cause of pollution [ 9 ]. Whereas CSVP still contains some nutrients (60 % carbohydrates and 2.2 % crude protein), it may be fed to animals [ [10] , [11] , [12] ]. However, the use of CSVP was still limited due to its low protein content (2.17 % crude protein) and high fiber content, specifically cellulose at 20.65 % and lignin at 4.08 % [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cassava pulp (CSVP) is a residue of the starch manufacturing process, which could produce up to 500 tons of CSVP per day and might be a cause of pollution [ 9 ]. Whereas CSVP still contains some nutrients (60 % carbohydrates and 2.2 % crude protein), it may be fed to animals [ [10] , [11] , [12] ]. However, the use of CSVP was still limited due to its low protein content (2.17 % crude protein) and high fiber content, specifically cellulose at 20.65 % and lignin at 4.08 % [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The production, development, and metabolism of microorganisms during acidogenesis fermentation require an optimal carbon-to-nitrogen (C/N) ratio [ 24 ]. Recent research by Pongsub et al [ 10 ] indicated that CSVP fermented with Lactobacillus casei TH14 ( L. casei TH14), urea, and molasses recovered DM, had fewer aerobic bacteria, and contained more LAB. In addition, the research recommended fermenting CSVP for 21 days since it produced a larger amounts of crude protein (CP) and lactic acid than other procedures [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it immediately spoils and emits an unpleasant and strong scent. Moreover, the use of cassava pulp has been proposed in various applications, such as animal feeds ( Diarra and Devi, 2015 ; Dagaew et al, 2022 ; Pongsub et al, 2022 ), bioethanol ( Rattanachomsri et al, 2009 ; Siriwong et al, 2019 ), succinic acid ( Sawisit et al, 2015 ), lactic acid ( Thongchul et al, 2010 ; Gali et al, 2021 ), fertilizer ( Phun-iam et al, 2018 ; Hasanudin et al, 2019 ), biogas ( Lerdlattaporn et al, 2021 ), biodegradable polymer ( Hierro-Iglesias et al, 2022 ) and biocomposites ( Nguyen et al, 2020 ; Nithikarnjanatharn and Samsalee, 2022 ). Clearly, high value-added products can be created from leftover cassava wastes generated by the cassava industry.…”
Section: Introductionmentioning
confidence: 99%